The Role of Religious Coping in Caregiving Stress - Lidya Triana; Iwan Gardono Sudjatmiko (Religions, 2021)
Studies explaining how stressors and religious coping affect caregivers’ depression have been rarely conducted in the Indonesian context. Therefore, this study discusses stress process theory by examining the role of religious coping as a moderating variable between relational deprivation and loss of self on depression. In a quantitative study of 50 caregivers of persons with schizophrenia in Indonesia, this study analyzed the moderating variables using multiple regression. The results showed that higher relational deprivation will lead to increased depression, but religious coping mechanisms can reduce the effect of relational deprivation on depression (buffering effect). Religious coping can also minimize the effect of loss of self to depression. Subjective stressors and religious coping offer new theoretical insights and must be considered when studying caregiving stress. In this regard, mental health services aiming to enhance caregivers’ welfare need to be provided by the state and community.